Artistic Speech Possibilities and Author's Skills in Character Creation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the author emphasizes the issues of creating a character in a work of art. In particular, the character's way of speaking, speech, behavior, clothes, mutual description, self-description, etc., are analyzed in depth, and examples from the creative works of Stefan Zweig and Ulugbek Hamdam are given.